Spatial variability of total porosity, moisture and soil resistance to penetration of a yellow ultisol - Mion, Renildo Luiz; Nascimento, Elivânia Maria Sousa; Sales, Francisco Alexandre de Lima; Silva, Silvia Ferreira da; Duarte, José Moacir Lima; Sousa, Beatriz Marques de (Semina: Ciências Agrárias, 2012)
The study of spatial variability of soil attributes is important in areas under different uses and management. The moisture and soil resistance to penetration are considered an indicative parameter of soil physical quality. The objective of this work to study the spatial variability of total porosity, soil resistance to penetration and moisture in an area of rotational grazing sheep. The experiment was conducted in a Yellow Ultisol with a sandy texture in the layers of 0- 0.1, 0.1-0.2 and 0.2-0.3 m. For the determination of properties and soil resistance to penetration was defined a grid, with regular intervals of 30 m, total of 13 points. The total porosity (TP) and the gravimetric soil moisture (SU) were obtained by collecting undisturbed samples (Uhland soil sampler) and disturbed samples, respectively. The soil resistance to penetration (PR) was determined at each point using an electronic georeferenced penetrometer. The results showed that TP had a low variation coefficient in all studied layers. The SU in all evaluated layers and the PR in layers 0-0.1 and 0.1-0.2 m showed a medium variation coefficient. The PR in layer 0.2-0.3 m showed a high variation coefficient showing the average distribution with a high heterogeneity in the data. The attributes TP, PR and SU showed a weak spatial dependency index (SDI) in all evaluated layers. The PR increases as the TP and the SU has a smaller influence on the soil.